Stabilitas Permintaan Uang di Indonesia Sebelum dan Sesudah Perubahan Sistem Nilai Tukar - Sahabudin Sidiq (Universitas Islam Indonesia, 2005)
The objective of this study is to analyze the stability of money demand in Indonesia before and after the change of exchange rate system, from managed floating exchange rate to free floating exchange rate in the middle of 1997. And also to analyze the role of exchange rate on the money demand in Indonesia.The result shows that there are no change in stability of money demand for M1 and any change in stability for M2. The role of exchange rate is very significant in money de¬mand in Indonesia not only for M1 but also for M2. Because of right now, the exchange rate system is free floating exchange rate, where no government intervening, so that the govern¬ment should to maintain the exchange rate market more efficient.Keywords: Money Demand, Managed floating exchange rate, free floating exchange rate, stability of money demand